[OP.1B.03] IDENTIFICATION OF A CUT-OFF LEVEL OF URIC ACID ASSOCIATED WITH VASCULAR STIFFNESS IN A GENERAL POPULATION. (September 2016) - Di Leva, A.; Koretzky, M.; Obregon, S.; Pardini, P.; Maccallini, G.; Haehnel, M.; Huguet, E.; Botto, F.; Scuteri, A.; Nilsson, P.M.; Kotliar, C.
Abstract : Objective: The role of uric acid (UA) in the development of hypertension and atherosclerosis has been extensively studied. In regard to vascular stiffness, UA has demonstrated an independent association with age, gender, obesity, blood pressure and renal function. However, research has focused on the relationship between UA elevation and high blood pressure or atherosclerosis in hypertensive and renal failure patients. Recent data from the Framingham cohort, showed that this association persists in the general population. However there is no clear evidence of the cutoff level above which UA has a predictive value for vascular stiffness. Objective: To evaluate the relationship between UA and vascular stiffness in a general population, and to determine the cutoff level of serum uric acid for this association. Design and method: We recruited consecutively individuals without previous cardiovascular events, who attended a medical center for cardiovascular risk assessment. A blood sample was obtained and vascular stiffness was determined by the measurement of pulse wave velocity (PWV) using the Mobil-O-Graph (Germany). We excluded those diagnosed with gout, diabetes, renal failure, malignancies, and use of drugs for hyperuricemia. The population was categorized in quartiles of uric acid and PWV. The association of PWV and UA was explored by adjusted multiple regression. The cut-off level for the association of UA and PWV (abnormal vascular stiffness >=10 m/sec) was determined by ROC curve analysis (sensitivity - [1-specificity]). Results: We included 129 subjects (age 52.5 ± 13.8 years, 40% women). Mean serum UA was 333.09 ± 220.08 mMol/L, and the PWV averaged 8.9 ± 4.5 m/sec. The association between UA and PWV remained independent after adjusting for body mass index, smoking and blood pressure. Finally the best cutoff level for UA associated with the highest quartile of PWV was 458 mMol/L (discrimination value of 0.7). Conclusions: We observed a significant association between UA and vascular stiffness in a general population. The serum UA cut-off point was 458 mMol/L. These results encourage lines of research aimed at reducing UA levels in order to improve arterial stiffness.